SISTEM DAN PROSEDUR PENYALURAN KREDIT USAHA RAKYAT KEPADA UMKM OLEH PT BANK MANDIRI (PERSERO) TBK CABANG TANJUNGPURA PONTIANAK - Amelia Amelia; Dewi Oktary (Jurnal Ekonomi Integra, 2022)
The purpose of this research is to analyze the system and distribution procedure of People’s Business Credit to Micro, Small and Medium Enterprises given by Bank Mandiri Inc., Tanjungpura Pontianak Branch. This research applies descriptive research with qualitative approach. Based on the results of this research shows that the system and distribution procedure of People’s Business Credit (KUR) to Micro, Small, and Medium Enterprise (MSME) given by Bank Mandiri Inc., Tanjungpura Pontianak Branch has been done properly starting from credit application, credit analysis covering 5C, credit grant decisons, up to loan disbursement. Supervision has been effectively done with Preventive Control which is a supervision through field observation before loan disbursement and also does Repressive Control which is a supervision done after loan disbursement and during credit usage to all debtors to maintain their business conditions with hope of avoiding deviations and bad credit loans.